Analysis of Spiritual Care Competence in Students of Ferdows Health and Paramedical School: 2014-15 - E Yazdan Parast; SS Afrazandeh; H Ghorbani; F Asadi; R Rajabi; L Naseri; F Sekandari (Iran University of Medical Sciences, 2017)
Abstract Background & Aim: Spiritual care is an important aspect of health care which has been considered during recent decades. Spiritual care should be considered as an important part of holistic care. Having competency is necessary for delivering good level of spiritual care to patients. The present study has been carried out in order to investigate the spiritual care competence in students at Ferdows Health and Paramedical School during 2014-15. Materials & Methods: This was a cross-sectional descriptive study. The study population included 240 students at Ferdows Health and Paramedical School. Finally, 190 students, who volunteered to participate in the study, were studied as the study samples. Data about students' competency in spiritual care were collected, using Spiritual Care Competence Scale. Research data were analyzed using SPSS version 16. Results: The mean score of students' spiritual care competency was 101.72 ± 12.69 which indicates that students have a high level of competencies in spiritual care. Independent t-test showed no significant relationship between the mean of spiritual care competency and other parameters such as gender (P = 0.31), marital status (P = 0.1), housing status (P = 0.36), history of clinical practice (P = 0.64). ANOVA test showed that there is a significant difference between the mean scores of spiritual care competency and different academic semesters (P = 0.03). Conclusion: Reinforcing ethical and spiritual foundations of student's role models (such as professors), programming a unified plan, applying educational strategies, and making emotional educational atmosphere accompanied by trustee people will facilitate spiritual care.